The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fendo.2020.00497
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Non-linear Correlations Between Serum Phosphate Level and Bone Mineral Density in Type 2 Diabetes

Abstract: Introduction: Serum phosphate plays an important role in bone mineralization and might be a risk factor for many bone diseases. Patients with T2D usually have low serum phosphate level due to diet control, osmotic diuresis, and insulin stimulation. Current studies have discussed the linear association between serum phosphate and bone mineral density (BMD). Objective: We aimed to analyze both the linear and non-linear correlations between serum phosphate and BMD in patients with type 2 diabetes (T2D). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There was a significant positive correlation between serum phosphorus and TH BMD. Previous studies have shown that relatively high blood phosphorus levels in the normal range may be beneficial to BMD (37). Phosphate is important for osteoblast differentiation and extracellular matrix mineralization, with its level directly affecting bone metabolism (38).…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant positive correlation between serum phosphorus and TH BMD. Previous studies have shown that relatively high blood phosphorus levels in the normal range may be beneficial to BMD (37). Phosphate is important for osteoblast differentiation and extracellular matrix mineralization, with its level directly affecting bone metabolism (38).…”
Section: Discussionmentioning
confidence: 99%